Virgulino : proposta lúdica de ensino do uso da vírgula - Oliveira, Luciana da Cruz (2021)
Among the many challenges that public schools have been facing over the years facing over the years, one of the most common by both teachers and researchers is the teaching of writing. Students, especially in the final years of elementary school II, present several difficulties (SAEB, 2017), among them the inadequate use of punctuation, particularly, the comma. In this research, based on samples of productions of 7th grade students from a year of a public state school in the municipality of Itabaiana, the goal was to create a pedagogical product that would help the student to develop an understanding of the role of the comma in the cohesion process (FÁVERO, 2000; GOMES, 2009). The elaboration of a didactic sequence (DOLZ, NOVERRAZ, SCHNEUWLY, 2004) aimed to the development of competencies for the use of punctuation, especially, the comma (DAHLET, 2006; 2002), in the practice of production and interpretation of expected from students of 7th grade of elementary school. Within this sequence was developed a learning object (AGUIAR; FLORES, 2014), a card game that combines the verbal and the imagetic, ie, that is based on the multimodal vision (CAPISTRANO, 2017) of human communication. This choice arises from the need to expand the range of alternatives for actions that consider multisemiosi (GOMES, 2018) and playfulness (FADEL; ULBRICHT; BUSARELO, 2014) as relevant allies in the learning process. This work was also based on the discussions of Koch (1999, 2011), when dealing with the notion of text and the scope of textual linguistics, in dialogue with the perspectives of Marcuschi (2005, 2008) and Antunes (2003, 2009).